A Phantom Menace? Patents and The Communal Status of Space - Smith, Tim (Victoria University of Wellington Law Review, 2003)
This paper provides an analysis of the interaction between the most important intellectual property right for the space industry, patents, and the international status of space as a "common area". It suggests that the conventional thesis upon which the application of domestic patent laws to space-based activities rests is an incomplete analysis of the legal interaction. A fundamental conflict between patent rights over inventions that make use of the intrinsic properties of the space environment is identified, and the implications of this conflict discussed. While the application of domestic patent law to space-based activities is nonetheless almost certainly legitimate as a matter of international law, this paper argues that the combined effect of States' patent grants over spacebased inventions is to undermine the status of space as a "common area".